INSTAGRAM STORIES FROM THE PERSPECTIVE OF NARRATIVE TRANSPORTATION THEORY - UZUNÇARŞILI SOYDAŞ, AYDA (ISTANBUL KULTUR UNIV, 2017)
Stories, which have been important parts of social life for centuries, are narratives that keep social memory alive. With developments in communication technology, many of its constituents like its format, transfer speed, environments and size have changed and developed. Especially the narratives that have emerged through the effects of social media and have started to form a new century's new stories. This study analyzes that how the stories that are shared on Instagram create a sustainable story from the perspective of narrative transportation theory. In the research part of the study, a multidimensional analysis applies netnography and content analysis research techniques.
Keywords: Instagram; Narrative; Netnography; Storytelling; Memory